2017
DOI: 10.1589/jpts.29.863
|View full text |Cite
|
Sign up to set email alerts
|

Validity of using multi-frequency bioelectrical impedance analysis to measure skeletal muscle mass in preschool children

Abstract: [Purposes] Although it is recommended to develop a habit of physical activities, there is no easy way to measure skeletal muscle mass in preschool children, which cause the difficulty of evaluation. The purpose of this study was to examine the validity of body composition including the skeletal muscle mass assessment using multi-frequency bioelectrical impedance analysis by comparing body fat mass obtained by using multi-frequency bioelectrical impedance analysis method and body mass index formulas. [Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Comparable data for preschool-aged children and fatherchild population groups using the FFQ were also available and hence it was chosen for this current study [25,26,55]. While previous research has demonstrated validity of using bioelectrical impedance analysis for use in preschool-aged children [83], there have been no studies that have validated the model used in this current study (InBody 720) in preschoolaged children. As such, further validation studies are required in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable data for preschool-aged children and fatherchild population groups using the FFQ were also available and hence it was chosen for this current study [25,26,55]. While previous research has demonstrated validity of using bioelectrical impedance analysis for use in preschool-aged children [83], there have been no studies that have validated the model used in this current study (InBody 720) in preschoolaged children. As such, further validation studies are required in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Minimum wear-time of 3 days, 7 h/day [ 43 ] • Fathers : Montoye et al [ 44 ] = VM count cut-points; < 2,860 counts/min (sedentary); 2,860–3,940 counts/min (light); and ≥ 3,941counts/min (moderate-to-vigorous (MVPA). Minimum wear time of 4 days/ 7 h [ 43 ] Father-child co-physical activity • 2-items adapted from the Youth Media Campaign Longitudinal Survey [ 45 ] • Fathers reported on days per week they were physically active with their child one-on-one and with one or more family member Weight • Measured in light clothing, without shoes on a digital scale to 0.01 kg (model CH-150kp, A&D Mercury Pty Ltd, Australia) • Weight was recorded at least twice until two measures fell within a range of 0.1 kg, averaged for the analysis Height • Measured using the stretch stature method on an electronic stadiometer to 0.1 cm (model BSM370, Biospace, USA) • Height was recorded at least twice until two measures fell within a range of 0.3 cm, averaged for the analysis BMI • Calculated using the standard formula, weight (kg)/height in m 2 • Children’s BMI-z scores were calculated using age- and sex-adjusted standardized scores (z-scores) based upon the UK reference data [ 46 ] and LMS methods [ 47 ] • International Obesity Task Force cut points were used to determine overweight or obesity [ 48 ] Body composition • InBody720 bioelectrical impendence analyser, a multi-frequency bioimpedance device (Biospace Co., Ltd, Seoul, Korea) [ 49 ] Fathers only Physical Activity (Steps/day) • One week of pedometry using Yamax SW200 pedometers (Yamax Corporation, Kumamoto City, Japan). Validated in adults [ 40 ] • Asked to wear all waking hours (except when it could get wet or damaged) and to record steps on a log sheet for seven consecutive days • Daily step count averages were included in the final analysis if they had completed at least 4 days (3 weekdays and 1 weekend day) of pedometry Self-reported Moderate-to-vigorous physical activity (MVPA) • Average weekly MVPA measured using modified version of the Godin Leisure Time Exercise Questionnaire [ 50 ] • Participants reported average weekly bouts of moderate and vigorous physical activity and average bout length [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…BIA Bioelectrical Impedance Analysis is used to measure body composition. InBody 720 and S10 are medical-grade body composition analyzers, which rely on four technological milestones (8point tactile electrode system, direct segmental measurements, multiple frequencies, no estimations) to provide accurate and precise results that are highly correlated to gold-standard methods [13]. Our final results included three categories (low, normal or high) regarding BMI, muscle mass and body fat percentage (one by one) that has been shown to determine body composition independently of age, ethnicity or gender.…”
Section: Methodsmentioning
confidence: 99%